ChemInform Abstract: Orientational Ordering Studies of Fluorinated Thermotropic Liquid Crystals by NMR Spectroscopy. Issue 49 (9th December 2014) - Calucci, Lucia; Geppi, Marco; Urban, Stanislaw
Abstract Review: 43 refs.